2014
DOI: 10.1186/1471-2377-14-104
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of subcortical grey matter abnormalities in patients with MRI-negative cortical epilepsy determined through structural and tensor magnetic resonance imaging

Abstract: BackgroundAlthough many studies have found abnormalities in subcortical grey matter (GM) in patients with temporal lobe epilepsy or generalised epilepsies, few studies have examined subcortical GM in focal neocortical seizures. Using structural and tensor magnetic resonance imaging (MRI), we evaluated subcortical GM from patients with extratemporal lobe epilepsy without visible lesion on MRI. Our aims were to determine whether there are structural abnormalities in these patients and to correlate the extent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 35 publications
2
11
0
2
Order By: Relevance
“…Wang et al () investigated decreases and increases in FA in regions such as the entorhinal‐hippocampal area, amygdala, thalamus, striatum, accumbens, and neocortex in methionine sulfoximine‐infused rats as model of human MTLE. Peng et al () observed altered diffusion parameters of subcortical gray matter in patients with MRI‐negative cortical epilepsy using DTI, and reported the decrease in FA values in the bilateral nucleus accumbens in epilepsy patients for the first time. The decreases in FA using DTI are known to occur in gray matter areas during cerebral ischemia and sustained seizures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al () investigated decreases and increases in FA in regions such as the entorhinal‐hippocampal area, amygdala, thalamus, striatum, accumbens, and neocortex in methionine sulfoximine‐infused rats as model of human MTLE. Peng et al () observed altered diffusion parameters of subcortical gray matter in patients with MRI‐negative cortical epilepsy using DTI, and reported the decrease in FA values in the bilateral nucleus accumbens in epilepsy patients for the first time. The decreases in FA using DTI are known to occur in gray matter areas during cerebral ischemia and sustained seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some recent clinical studies provided initial evidence for the safety and feasibility of chronic electrical stimulation of the NAc in patients with intractable partial epilepsy, as indicated by largely unchanged neurocognitive function and psychiatric comorbidity (Kowski et al, ; Schmitt et al, ). Peng et al () reported the first evidence of structural abnormalities in the nucleus accumbens along with other subcortical gray matter in patients with MRI‐negative extemporal lobe cortical epilepsy. These findings, together with our results, strongly support the role of the NAc shell in epileptogenesis from distinct perspectives.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,32,47,48 The same loops are implicated as anatomical correlates of myoclonus. 49 In a sample of 43 JME patients, 42% reported asymmetric or unilateral myoclonic jerks. 6 Interestingly, Peng et al found a reduced right putaminal volume in epileptic patients with normal brain imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative imaging can also define the total volumes of gray and white matter in each lobe, which may also inform the trained observer that a subtle lobar abnormality exists that could not be appreciated on direct inspection. 15 Qualitative evaluation is currently in clinical use, while quantitative automated methods remain under investigation. 16,17…”
Section: Volumetric Analysismentioning
confidence: 99%